Pay for prudence - Arif, Salman; Donovan, John; Gopalan, Yadav; Morris, Arthur (Journal of Accounting and Economics, 2024)
We provide the first evidence that prudential principles shape bankers' executive compensation, a phenomenon we call “pay for prudence” (PfP). We conjecture that PfP incentivizes bankers to balance shareholders' preference for risk with regulators' preference for prudence. Although PfP terms are often used in bank compensation contracts, we find that the use of detailed and concrete PfP terms are positively associated with equity incentives for risk-taking. Furthermore, detailed and concrete PfP terms are associated with lower tail risk, fewer bad loans, and lower likelihood of regulatory downgrades. While we do not find evidence that PfP is associated with lower profitability, PfP is associated with more diversified loan portfolios and reduced exposure to real estate. Our results shed light on a new dimension of bankers' pay and suggest that PfP-based incentives complement widely studied equity-based incentives for risk-taking by acting as guard rails that guide managers’ pursuit of investment opportunities.